Stage-structured plastisphere succession sustains antibiotic resistomes on microplastics during full-scale A2/O wastewater treatment - Xin Hou; Xiaoran Li; Yunan Lin; Xiaoyan Li; Wen Li; Lei Zhang; Jiamin Li; Ziming Jiang; Sen Wang; Xiaotong Wang; Xianhua Liu (Water Research, 2027)

Atomic-scale matrix partitioning of polar and antipolar motifs for high-density energy storage capacitors - Dingheng Lin; Bin Kong; Jinjun Liu; Jiarong Lv; Ya Yang; Wei Zhang; Sen Chen; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Soil quality degradation induces synergistic evolution of carbon components: Microbial extracellular polymeric substances - driven mechanism - Renjie Hou; Sisi Liu; Anshuang Su; Miao Wang; Hai Wang; Sen Lin; Xin Zhao; Xu Leng; Jian Zhang; Lan Luo; Chunjiao Wang (Journal of Environmental Management, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Antimicrobial and Antitumor Activities of Endophytic Fungi from the Medicinal Plant Paris polyphylla var. yunnanensis - Jing Zhang; Hao-Lin Yu; Yu Zhang; Chen-Sen Xu; Chao Wang; Yi-Lin Liu; Yi-Bo Shen; Jin-Zhong Hu; Zhi-Xin Liao (Current Microbiology, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Biodegradation of tetracycline antibiotics: Advances and insights into microbial resources, enzymatic mechanisms, and remediation potential - Aojie Lei; Mengyao Wang; Yaxin Pei; Qipeng Cheng; Hongyuhang Ni; Sen Yang; Hui Lin; Xinyu Liu; Hongge Chen (Journal of Hazardous Materials, 2026)

Duration of high temperature-pressure conditions in impact-induced plumes on the Moon - Xiaoying Liu; Chi Zhang; Zongyu Yue; Lixin Gu; Jing Li; Heng-Ci Tian; Sen Hu; Yangting Lin (Icarus, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Ti3C2 MXene-Based composites for photocatalytic antibiotic degradation: Etching strategies, mechanistic insights, and future perspectives - Zeng Liu; Siao Zhang; Yanling Guan; Sen Wang; Chunpeng Leng; Yue Yuan; Lin Liu; Guozhu Bo; Yong Yang; Fuping Li; Hao Wang (Journal of Environmental Management, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

A Novel Algorithm for Optimizing Structure of In-Situ Supplementary Irrigation Device for Afforestation in Dryland - Bokun Jia; Sen Zhai; Lin Zhang; Lijie Liu; Yong Yang; Xufei Liu; Shoujun Wu; Xin Hui (Water Resources Management, 2026)

Alterations in Gut Microbiota and their Association with Colonic Permeability and Inflammation in LPS-induced Sepsis Mice - Mengke Zhang; Yanyan Shu; Jingnan Yang; Sen Sang; Xiaoming Liu; Yuxia Li; Changjiang Qin; Lei An; Xuhong Lin (Current Microbiology, 2026)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

Mechanism and Treatment Effect of Antibiotic Resistance Genes in Wastewater During Constructed Wetland Operation - Zeng Liu; Siao Zhang; Yanling Guan; Sen Wang; Xi He; Chunpeng Leng; Yunlong Zhou; Yue Yuan; Lin Liu; Fuping Li; Hao Wang (Water Conservation Science and Engineering, 2025)

Microstructure-property relationships in Cu/N-TiO₂ photocatalytic concrete for marine applications: Role of preparation strategies - Guoliang Lin; Mengchen Huang; Sen Chen; Kun Li; Kun Han; Minyi Liu; Yuxiang Li; Wenhua Chen (Journal of Environmental Chemical Engineering, 2025)

Detoxifying zinc oxide nanoparticles during sludge anaerobic digestion in the presence of polyferric sulfate - Yongkui Yang; Junxiang Huang; Sen Qu; Guangxue Wu; Yiwen Liu; Yifeng Ling; Peizhe Sun; Yingxin Zhao; Lin Zhao (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Stability of cement-red soil ecological substrate slope under simulated rainfall conditions: experiment and finite element analysis - Guoliang Lin; Sen Chen; Pengpeng Jiang; Mengchen Huang; Xiaoyi Zhang; Wanxi Jiang; Aoxiang Lin; Minyi Liu (Bulletin of Engineering Geology and the Environment, 2025)

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

Localized chemical disorder induced superior energy storage performance of PbZrO3-based antiferroelectric ceramics - Mingqi Shi; Xingke Pan; Dingheng Lin; Ning Liu; Wei Zhang; Sen Chen; Peng Li; Jinjun Liu; Hongzhen Xie; Zhongbin Pan (Chemical Engineering Journal, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Synergistic atmospheric influence on the co-pyrolysis of antibiotic sludge and waste bicycle tires: Optimal drivers, products, and pathways - Dajie Jia; Tao Chen; Liangzhon Li; Jingyong Liu; Zhibin Chen; Sen Lin; Guopeng Ke; Fatih Evrendilek; Wuming Xie; Wenxiao Huang; Chenyu Yang (Journal of Hazardous Materials, 2025)

Identification of forest priority conservation and restoration areas for different SSPs-RCPs scenarios - Miaomiao Liu; Shuang Liu; Raohan Tang; Minggao Liu; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Environmental Management, 2025)

Atmosphere-dependent pyrolytic transformability of glass fiber/epoxy resin composites in waste wind turbine blades - Siqi Chen; Jingyong Liu; Ziting Lin; Sen Lin; Liangzhong Li; Yan Chen; Fatih Evrendilek; Weixin Li; Wenxiao Huang; Chenyu Yang; Haoran Yuan; Yao He; et al. (Chemical Engineering Journal, 2025)

Depositional record of metal(loid)s since late quaternary in the Laizhou Bay, China - Longlong Liu; Junfeng Gao; Shengjiang Zhang; Sen Lin; Dongdong Lu; Jialin Zhang; Xiang Xie; Bin Chen; Jiandong Qiu (Frontiers in Marine Science, 2025)
The contamination of marine ecosystems with metal(loid)s is an increasing environmental concern, largely driven by anthropogenic activities, and poses a significant risk to the health of ecosystems and human well-being. Geochemical background values represent the typical concentrations of trace elements observed in the natural environment. The utilization of disparate background values gives rise to disparate evaluation outcomes. The objective of this study was to investigate the concentration profiles of metal(loid)s (Cu, Pb, Zn, Cr, Cd, As, and Hg) along a sediment core in order to obtain background values and assess the depositional processes and contamination levels in Laizhou Bay. With the exception of arsenic, the distribution patterns of the remaining metal(loid)s were similar and could be divided into four stages, which were primarily influenced by the mean grain size and sediment sources. The results of the analysis of multiple indicators indicated that there was no evidence of heavy metal enrichment or contamination in the core sediments. Furthermore, the data demonstrated that all metal(loid)s present were of natural origin. The historical changes in metal(loid)s in the core sediments were predominantly linked to the sedimentary environment, sediment sources, and mean grain size. The mean values of the metal(loid)s in the DU 4-2 unit, formed during the Early Holocene, may be regarded as reference values for background concentrations.

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Inequality repercussions of roads on the coupling relationships between carbon supply and demand - Guanmin Liang; Miaomiao Liu; Minggao Liu; Min Wu; Xueman Zuo; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Cleaner Production, 2025)

A crazy trio in Parkinson's disease: metabolism alteration, α-synuclein aggregation, and oxidative stress - Sheng Li; Yanbing Liu; Sen Lu; Jiayi Xu; Xiaokun Liu; Di Yang; Yuxuan Yang; Lin Hou; Ning Li (Molecular and Cellular Biochemistry, 2025)

Fe2O3, Al2O3, or sludge ash-catalyzed pyrolysis of typical 3D printing waste toward tackling plastic pollution - Ziting Lin; Jingyong Liu; Liangzhong Li; Haiming Cai; Sen Lin; Fatih Evrendilek; Siqi Chen; Xin Chen; Tao Chen; Yao He (Journal of Hazardous Materials, 2024)

Interfacial Mo-N bonding enhancement of N-doped carbon nanosheets-stabilized ultrafine MoS2 enable ultrafast and durable sodium ion half/full batteries - Dongfei Sun; Sen Lin; Shengxu Kuai; Tiantian Zhang; Lei Liu; Jingxin Zhao; Xiaozhong Zhou; Wenwen Liu; Bingang Xu (Chemical Engineering Journal, 2024)

On the FT-ICR mass spectrometry analysis of dissolved organic matter released by adsorbent during coal chemical wastewater treatment - Qi Wei; Cai Chen; Hong-Peng Ma; Tao Liu; Bing Liu; Tian-Xiang Wang; Sen Zhang; Dan-Hui Yang; Wen-Jie Lv; Hua-Lin Wang (Science of The Total Environment, 2024)

Bimetallic MIL-68(InFe) MOF nanorods for biomimetic photocatalytic N2 fixation - Cheng Liu; Mengning Chen; Yueling Chen; Qi Chen; Jionghua Wu; Sen Lin; Ling Wu; Jimmy C. Yu (Chemical Engineering Journal, 2024)

Specific adsorption of antiviral drugs on ionic liquid-modified metal–organic framework: Adsorption behavior, mechanism, and DFT analysis - Yihan Li; Lin Zhao; Daying Chen; Tapas Sen; Guining Lu; Jiashu Liu; Xiaodong Du; Peizhe Sun; Yongkui Yang (Chemical Engineering Journal, 2024)

Entire co-combustion lifecycle of sewage sludge and water lettuce (Pistia stratiotes L.) and its controls over energetic and environmental benefits - Jiayu Liang; Jingyong Liu; Fatih Evrendilek; Zhibin Chen; Liangzhong Li; Sen Lin; Ziting Lin; Lei Li; Xieyuan Wu; Li Wang; Yao He (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Physicochemical, thermodynamic, and kinetic controls on volatile products, bio-oils, and biochars of Lycium barbarum pyrolysis and their multi-objective optimization - Siqi Chen; Sen Lin; Shengzheng Huang; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Yao He; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Jingyong Liu (Fuel, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Atmosphere-dependent combustion of Ganoderma lucidum biomass toward its enhanced transformability into green energy - Hanlin Cao; Hongda Zhan; Jianying Qi; Sen Lin; Mingzhong Ren; Jiayu Liang; Fatih Evrendilek; Yao He; Jingyong Liu (Environmental Science and Pollution Research, 2024)

First discovery of impact-induced vapor deposition of native copper, FeCo alloy and digenite from Chang'e-5 lunar soil - Jing Li; Lixin Gu; Xu Tang; Xiaoying Liu; Sen Hu; Yangting Lin (Icarus, 2024)

Multiplicative effects of co-incineration of sewage sludge and wasted oyster shells in air, CO2, and steam atmospheres on P speciation and bioavailability and metal ecotoxicity - Jiayu Liang; Zhiwei Huang; Jingyong Liu; Sen Lin; Ziting Lin; Fatih Evrendilek; Wuming Xie; Guanzheng Zhuang; Yao He; Li Wang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Second-generation bioenergy to decouple fossil fuel dependency and environmental deterioration: Dynamic and optimal mechanisms and gas-to-ash products of combustion of Pennisetum hydridum - Sen Lin; Li Wang; Jingyong Liu; Zebin Wei; Fatih Evrendilek; Jiayu Liang; Ziting Lin; Zuoyi Yang; Sheng Zhong (Biomass and Bioenergy, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Sulfur bacteria-reinforced microbial electrochemical denitrification - Sen Lin; Wentao Tang; Yihang Xiao; Feixiang Zan; Xiaoming Liu; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2024)

Intrinsic peroxidase-like clay mineral nanozyme-triggered cascade bioplatform with enhanced catalytic performance - Ke Wang; Shiyong Sun; Yevgeny Aleksandrovich Golubev; Sen Lin; Jin Liu; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Applied Clay Science, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Well-oriented immobilized immunoaffinity magnetic beads for detection of fumonisins in grains and feeds via pre-column automatic derivatization of high-performance liquid chromatography - Jinnan Chen; Meng Wang; Sen Li; Jin Ye; Li Li; Yu Wu; Di Cai; Tongtong Liu; Lin Zhu; Yi Shao; Songxue Wang (Food Chemistry, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Combustion mechanism and ash-to-gas products of star anise residues: Atmosphere and temperature dependencies and joint optimization - Tao Chen; Xiaoming Li; Jiayu Liang; Fatih Evrendilek; Xiaocui Wen; Sen Lin; Jingyong Liu (Fuel, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Bile acids and their receptors in regulation of gut health and diseases - Sen Lin; Sutian Wang; Peng Wang; Cuiming Tang; Zhenjiang Wang; Lian Chen; Guoqing Luo; Hong Chen; Yuntao Liu; Bin Feng; De Wu; Douglas G. Burrin; et al. (Progress in Lipid Research, 2023)

Study on the Coal–rock Ratio Effect of Asymmetric Deformation and Failure of the Gob–side Coal–rock Roadway in Gently Inclined Coal Seam - Lin Gao; Yexing Shen; Ping Liu; Yongyin Wang; Zhenqian Ma; Xiangtao Kang; Sen Han (Geotechnical and Geological Engineering, 2023)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Arsenopyrite oxidative dissolution in NaCl solution at high-temperature and high-pressure conditions: kinetics, pathways, dissolution mechanism and geological implications - Qingyou Liu; Kai Zheng; Shuai Wang; Luying Wang; Sen Lin; Heping Li (Contributions to Mineralogy and Petrology, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Long‐term nitrogen input alters plant and soil bacterial, but not fungal beta diversity in a semiarid grassland - Weixing Liu; Lingli Liu; Xian Yang; Meifeng Deng; Zhou Wang; Pandeng Wang; Sen Yang; Ping Li; Ziyang Peng; Lu Yang; Lin Jiang (Global Change Biology, 2021)
Anthropogenic nitrogen (N) input is known to alter plant and microbial α‐diversity, but how N enrichment influences β‐diversity of plant and microbial communities remains poorly understood. Using a long‐term multilevel N addition experiment in a temperate steppe, we show that plant, soil bacterial and fungal communities exhibited different responses in their β‐diversity to N input. Plant β‐diversity decreased linearly as N addition increased, as a result of increased directional environmental filtering, where soil environmental properties largely explained variation in plant β‐diversity. Soil bacterial β‐diversity first increased then decreased with increasing N input, which was best explained by corresponding changes in soil environmental heterogeneity. Soil fungal β‐diversity, however, remained largely unchanged across the N gradient, with plant β‐diversity, soil environmental properties, and heterogeneity together explaining an insignificant fraction of variation in fungal β‐diversity, reflecting the importance of stochastic community assembly. Our study demonstrates the divergent effect of N enrichment on the assembly of plant, soil bacterial and fungal communities, emphasizing the need to examine closely associated fundamental components (i.e., plants and microorganisms) of ecosystems to gain a more complete understanding of ecological consequences of anthropogenic N enrichment.

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Influencing factors of consumers’ willingness to purchase green housing: a survey from Shandong Province, China - Peidong Sang; Haona Yao; Lin Zhang; Sen Wang; Yanjie Wang; Jinjian Liu (Environment, Development and Sustainability, 2020)

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Removal of aqueous fluoroquinolones with multi-functional activated carbon (MFAC) derived from recycled long-root Eichhornia crassipes: batch and column studies - Lili Liu; Xin Chen; Zhiping Wang; Sen Lin (Environmental Science and Pollution Research, 2019)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Genotype imputation for Han Chinese population using Haplotype Reference Consortium as reference - Yuan Lin; Lu Liu; Sen Yang; Yun Li; Dongxin Lin; Xuejun Zhang; Xianyong Yin (Human Genetics, 2018)

Using network to enhance the insights on correlation and pollution assessment of co-occurring metals in marine sediments, the East China Sea - Lili Liu; Yupeng Wang; Sen Lin; Hong Li; Xin Chen; Zhiping Wang; Kuangfei Lin (Environmental Science and Pollution Research, 2018)

Calcification response of Pleurochrysis carterae to iron concentrations in batch incubations: implication for the marine biogeochemical cycle - Xiang Zou; Shiyong Sun; Sen Lin; Kexuan Shen; Faqin Dong; Daoyong Tan; Xiaoqin Nie; Mingxue Liu; Jie Wei (Frontiers of Earth Science, 2017)

Enhanced production of fructosyltransferase in Aspergillus oryzae by genome shuffling - Shenghai Wang; Mengjie Duan; Yalan Liu; Sen Fan; Xiaoshan Lin; Yi Zhang (Biotechnology Letters, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A simple method to extract tropical monsoon forests using NDVI based on MODIS data: A case study in South Asia and Peninsula Southeast Asia - Sen Lin; Ronggao Liu (Chinese Geographical Science, 2016)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

Two new ursolic acid saponins from Morina nepalensis var. alba Hand-Mazz - Zhi-feng Zhang; Lu-yang Lu; Pei Luo; Lin-sen Qing; Yuan Liu (Natural Product Research, 2013)

Pollution and variation of stream nitrate in a protected high-mountain watershed of Central Taiwan: evidence from nitrate concentration and nitrogen and oxygen isotope compositions - Tsung-Ren Peng; Hsing-Juh Lin; Chung-Ho Wang; Tsang-Sen Liu; Shuh-Ji Kao (Environmental Monitoring and Assessment, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Numerical experiments investigating the orographic effects on a heavy rainfall event over the northwestern coast of Taiwan during TAMEX IOP 13 - Pay-Liam Lin; Yi-Leng Chen; Ching-Sen Chen; Che-Ling Liu; Ching-Ying Chen (Meteorology and Atmospheric Physics, 2011)

Role of high zinc levels in the stress defense of common carp - Tzu-Yung Lin; Yen-Hua Chen; Chien-Lin Liu; Sen-Shyong Jeng (Fisheries Science, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Purification and characterization of a novel neutral β-glucanase and an alkaline β-glucanase from an alkaliphilic Bacillus isolate - Sen-Lin Liu; Wei-Zhao Chen; Yong Wang; Gang Liu; Shao-Wen Yu; Miao Xing (World Journal of Microbiology and Biotechnology, 2008)

Using SSR markers to determine the population genetic structure of wild apricot (Prunus armeniaca L.) in the Ily Valley of West China - He Tian-Ming; Chen Xue-Sen; Xu Zheng; Gao Jiang-Sheng; Lin Pei-Jun; Liu Wen; Liang Qing; Wu Yan (Genetic Resources and Crop Evolution, 2007)

Effect of dietary lipid level on growth performance, feed utilization and body composition of grouper Epinephelus coioides juveniles fed isonitrogenous diets in floating netcages - ZHI LUO; Yong-Jian Liu; Kang-Sen Mai; Li-Xia Tian; Dong-Hui Liu; Xiao-Ying Tan; Hei-Zhao Lin (Aquaculture International, 2005)

Synthesis of (R)-2-trimethylsilyl-2-hydroxyl-ethylcyanide catalyzed with (R)-oxynitrilase from loquat seed meal - Shun-Rong Huang; Sen-Lin Liu; Min-Hua Zong; Ruo Xu (Biotechnology Letters, 2005)

Nitric oxide is not involved in the endotoxemia-induced alterations in Ca 2+ and ryanodine responses in mouse diaphragms - Shing-Hwa Liu; Jiun-Li Lai; Rong-Sen Yang; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)